City Information Modeling (CIM) and Smart Cities (SC): A Bibliometric Analysis with VOSViewer and R Software with Bibliometrix Package (2010-2020) - Logatti, Bruna; Nazareth, Cristian Roberto (National Journal of City Management, 2022)
The present paper aimed to carry out a bibliometric analysis using the VOSViewer and R software, and to discuss the results obtained from queries accomplished by combining the keywords City Information Modeling and Smart Cities, as well as their relationship in the contemporary context of cities. To this end, the Web of Science referential platform was adopted as a scientific database and the adopted filter published articles in English journals from 2010 to 2020. This way, the data obtained were downloaded and inserted into the mentioned software, which allowed the performance of qualitative and quantitative analyses. The sentences used in the research revealed certain particularities, from the elevated and constant production of scientific articles to the absence of publications regarding the direct use of the terms "CIM" and "Smart Cities". Therefore, the use of the proposed tools can contribute to the survey of specific studies in the area in question, as well as revealing research trends in the scientific environment and consequently its evolution in the academic scenario.